Extent, environmental impact and long-term trends in atmospheric contamination in the Usa basin of east-European Russian arctic - Solovieva, N; Jones, VJ; Appleby, PG; Kondratenok, BM (KLUWER ACADEMIC PUBL, 2002)
Sediment cores and surface sediments from fourteen lakes located along three pollution gradients in the Usa basin, north-east European Russia were analysed for diatoms, spheroidal carbonaceous particles, trace metals and water chemistry. At each site past pH was inferred using a diatom-based transfer function and critical loads for sulphur deposition were calculated using a diatom model. Lakes from the Vorkuta transect currently experience the highest levels of atmospheric deposition, however, results suggest that at present day sulphur deposition levels there is no danger of lake acidification at any of the sites, due to their high buffering capacity. The sediment records show that sites from the Inta and Vorkuta transects experienced higher pollution loads 10-30 yr ago, when coal production and mining were more intensive. There is also evidence that in the Vorkuta area atmospheric deposition might have led to the alkalisation of the lakes since diatom floristic changes and an increase in inferred pH coincide with the period of peak industrial activity.